Trajectory Planning considering Motion Sickness and Head Movements. Issue 14 (2022) - Steinke, Alexander; Konigorski, Ulrich
Abstract: A widespread trigger of discomfort in road vehicles is motion sickness (MS), which describes the motion induced occurrence of symptoms such as dizziness, nausea and vomiting. This paper presents an approach to consider MS in optimal trajectory planning for autonomous passenger vehicles. Optimization based planning is a well suited method as it explicitly considers hard constraints, e.g. road bounds, and ensures that the vehicle is able to follow the planned trajectory even at the limits of handling. However, solving the optimization problem numerically can be expensive especially with high order models. Complex models may even lead to poor convergence properties of the numerical algorithms. In this work, we propose a model incorporating passive head tilting and the subjective vertical conflict (SVC) model. We show that when assuming comfortable driving, significant simplifications can be done by approximating the vertical conflict as jerk. We embed the SVC model in the planning problem, and show that similar results are achieved when considering either vertical conflict or jerk. In any case, MS can be predictively suppressed even on roads that prone to trigger motion sickness.